Ionic liquids as designer molecules for XPS peak fitting - Clarke, Coby James (2016)
X-ray photoelectron spectroscopy (XPS) of ionic liquids (ILs) has become a valuable tool for the investigations of IL interfacial and physicochemical properties. The complex signals that result from elements which occupy a variety of chemical states, for example the C 1s photoemission, are often interpreted through chemical intuition and peak fitting parameters. This Thesis will present a new method to determine exact photoemission binding energies (B.E.s), through the comparison of multiple spectra. The designer aspect of ILs has been exploited in order to produce salts with small structural modifications. By comparing the C 1s and N 1s photoemissions of the structurally related samples, difference spectra have been produced. These spectra show the relative shifting of electron density between the two signals, revealing the initial and final locations of the changing photoemission. Using this technique, the current C 1s peak fitting models of imidazolium and pyridinium ILs have been examined. A variety of 4,4’-bipyridinium salts have also been used as a structural variation of pyridinium ILs to show how molecular symmetry and normalisation may be utilised in order to produce photoemissions equivalent to fragments of molecules. The subsequent C 1s difference spectra have provided carbon peak fitting models for mono- and di-alkylated 4,4’-bipyridinium salts. Without the use of XP difference spectra, these known fitting models would be almost impossible to determine. Finally, multiple complex difference spectra have been used to identify the exact B.E.s of C 1s photoemissions from a series of nitrile functionalised ILs. The complex difference spectra have also been analysed by inverse Gaussian fittings to show how additional information may be extracted from the characteristic shapes. The ‘construction’ of photoemissions is also demonstrated, whereby known B.E. peaks are assembled to accurately reproduce experimentally determined XP spectra.